Recent advances in virus imprinted polymers - Amorim, Mariana S. (2022)
Molecular imprinting is a mature and appealing technology to obtain highly selective recognition sites created within a polymeric network, having other important features such as robustness and cost effectiveness. The applications of molecularly imprinted polymers (MIPs) are vast, but there is a continuous particular interest in their integration into sensing devices. MIPs possess remarkable properties in terms of selectivity and low-cost of tailored biomimetic recognition elements. The need to improve disease diagnosis and prevention by detecting pathogenic viruses and other biological targets at the nanoscale has led to great advances in MIPs. Despite still facing many challenges, imprinting approaches can provide rapid and accurate virus recognition and thus be applied as new sensing materials. Following a general overview of MIP technology, key examples of virus imprinted polymers, the application of MIP-based materials to other nanoscale targets, and their detection are presented here. Perspectives and challenges are also highlighted foreseeing new future strategies and MIP designs.